2013
DOI: 10.1097/cnd.0b013e31829e22ba
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Chemosensation in Myasthenia Gravis

Abstract: Chemosensory dysfunction has been reported in a number of patients with myasthenia gravis. Given the close association between complaints of taste dysfunction and loss of flavor sensations secondary to olfactory system damage, quantitative testing should be used to accurately assess the nature and degree of the dysfunction present in this debilitating disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…Fourth, unquantified smell dysfunction has been reported from patients harboring synaptophysin and CGA dysfunction associated nasal dysfunction [42, 46, 47]. Fifth, olfactory disorders have been detected by patients suffering neural disorders-associated cholinergic neurotransmission days before their actual disease surfaced [48, 49]. Sixth, quick and impressive plastic changes of olfactory function following clinical improvement similar to the trend reported here have been found in disorders associated nanocholinergic dysfunction [48, 49].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Fourth, unquantified smell dysfunction has been reported from patients harboring synaptophysin and CGA dysfunction associated nasal dysfunction [42, 46, 47]. Fifth, olfactory disorders have been detected by patients suffering neural disorders-associated cholinergic neurotransmission days before their actual disease surfaced [48, 49]. Sixth, quick and impressive plastic changes of olfactory function following clinical improvement similar to the trend reported here have been found in disorders associated nanocholinergic dysfunction [48, 49].…”
Section: Discussionsupporting
confidence: 56%
“…Fifth, olfactory disorders have been detected by patients suffering neural disorders-associated cholinergic neurotransmission days before their actual disease surfaced [48, 49]. Sixth, quick and impressive plastic changes of olfactory function following clinical improvement similar to the trend reported here have been found in disorders associated nanocholinergic dysfunction [48, 49]. Seventh, the smell function in our patient was impaired before mass removal, regaining the olfactory function after surgical procedure, all of which was reflcted in the UPSIT scores.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the antibody generated by autoimmunity blocks the cholinergic receptors of the central nervous system. A number of studies have also confirmed this hypothesis by detecting the presence of acetylcholinergic receptors in the gustatory bud cells ( 8 ). Moreover, an animal-model experiment has shown that acetylcholine mediates the conduction of information between gustatory bud recipient cells and increases the activities of gustatory afferent neurofibers ( 9 ).…”
Section: Discussionmentioning
confidence: 83%
“…Case reports have anecdotally reported on chemosensory dysfunction in individuals with MG [35]. Leon-Sarmiento et al [26] proved, using the UPSIT, that MG patients had a clear smell loss.…”
Section: Discussionmentioning
confidence: 97%
“…P value was set at b 0.05. Results from olfactory testing can be analyzed separately from each other and/or as the sum of the scores from the three individual tests [32,35]. Since our aim was to determine olfactory and gustatory dysfunction, collapsed olfactory analyses were not done.…”
Section: Statistical Analysesmentioning
confidence: 99%